2016
DOI: 10.1021/acs.biomac.6b00185
|View full text |Cite
|
Sign up to set email alerts
|

A Rationally Optimized Nanoparticle System for the Delivery of RNA Interference Therapeutics into Pancreatic Tumors in Vivo

Abstract: Pancreatic cancer is a devastating disease with a dismal prognosis. Short-interfering RNA (siRNA)-based therapeutics hold promise for the treatment of cancer. However, development of efficient and safe delivery vehicles for siRNA remains a challenge. Here, we describe the synthesis and physicochemical characterization of star polymers (star 1, star 2, star 3) using reversible addition-fragmentation chain transfer polymerization (RAFT) for the delivery of siRNA to pancreatic cancer cells. These star polymers we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 47 publications
1
70
0
2
Order By: Relevance
“…In fact, the ability of βIVb-tubulin inhibition to sensitize PDA cells to vinca alkaloids also means that vinca alkaloid dosing could potentially be reduced in combination with βIVb-tubulin inhibition. We have also made significant advances in siRNA delivery technology [37], which not only overcomes the lack of specific inhibitors against βIVb-tubulin, but can also target therapy to PDA tumors. To highlight the therapeutic potential of targeting a single β-tubulin isotype up-regulated in PDA, we have previously administered therapeutic doses of βIII-tubulin siRNA with nanoparticle which effectively inhibited βIII-tubulin protein levels in orthotopic pancreatic tumors without any off-target toxicity in other organs in mice [37].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the ability of βIVb-tubulin inhibition to sensitize PDA cells to vinca alkaloids also means that vinca alkaloid dosing could potentially be reduced in combination with βIVb-tubulin inhibition. We have also made significant advances in siRNA delivery technology [37], which not only overcomes the lack of specific inhibitors against βIVb-tubulin, but can also target therapy to PDA tumors. To highlight the therapeutic potential of targeting a single β-tubulin isotype up-regulated in PDA, we have previously administered therapeutic doses of βIII-tubulin siRNA with nanoparticle which effectively inhibited βIII-tubulin protein levels in orthotopic pancreatic tumors without any off-target toxicity in other organs in mice [37].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MYH knockout mice, while viable, are 1.7 times more likely to develop spontaneous tumours, particularly in the intestines [35]. On this point, siRNA therapeutics coupled to cancer-targeting nanoparticles represent an ideal avenue for targeting MYH in PC cells, while overcoming the current lack of pharmacological inhibitors against MYH [3638]. …”
Section: Discussionmentioning
confidence: 99%
“…Notably, further in vivo studies have revealed a bright future for star polymers in gene therapy. [41,42] In addition to the biomedical applications noted in the present review, star polymers can also be employed in several other fields such as membrane science, catalysis, and photonics. Given the variety of potential applications for these versatile materials, we envision that, going forward, star polymers prepared using RAFT polymerization will continue to be the subject of considerable interest.…”
Section: Star Polymers For Imaging and Theranostic Applicationsmentioning
confidence: 99%
“…After systemic administration, the in vivo results indicated that the star polymer could efficiently deliver siRNA to orthotopic pancreatic tumours in mice and effectively inhibit the expression of bIIItubulin. [42] Notably, the gene delivery capability of PDMAEMA-based cationic star polymers was not compromised by employing other synthetic protocols for the star formation, such as an ATRP arm-first approach. [43] Compared with other drug and gene carriers self-assembled from amphiphilic molecules, the synthesis of star polymers is both time-and cost-effective.…”
Section: Star Polymers For Drug and Gene Deliverymentioning
confidence: 99%